Clinical audit research and evaluation of motor neuron disease (CARE-MND): a national electronic platform for prospective, longitudinal monitoring of MND in Scotland. Issue 3 (3rd April 2019) - Leighton, Danielle; Newton, Judith; Colville, Shuna; Bethell, Andrew; Craig, Gillian; Cunningham, Laura; Flett, Moira; Fraser, Dianne; Hatrick, Janice; Lennox, Helen; Marshall, Laura; McAleer, Dympna; et al.
Abstract: Objectives : Launched in 1989, the Scottish Motor Neuron Disease Register (SMNDR) has provided a resource for prospective clinical data collection. However, in 2015 we aimed to evolve a system to allow: i) A patient-centered approach to care based on recognized standards, ii) Harmonized data sharing between Scottish health professionals in "real-time", iii) Regular audit of care to facilitate timely improvements in service delivery, and iv) Patient participation in a diverse range of observational and interventional research studies including clinical trials. Methods : We developed a standardized national electronic data platform—Clinical Audit Research and Evaluation of MND (CARE-MND) which integrates clinical audit and research data fields. Data completion pre- and post-CARE-MND were compared, guided by recently published National Institute for Clinical Excellence (NICE) recommendations. Statistical difference in data capture between time periods was assessed using Z-test of proportions. Results : Data field completion for the historical 2011–2014 period ranged from 4 to 95%; median 50%. CARE-MND capture ranged from 32 to 98%; median 87%. 15/17 fields were significantly more complete post-CARE-MND ( p < 0.001). All MND nurse/allied health specialists in Scotland use the CARE-MND platform. Management of MND in Scotland is now coordinated through a standardized template. Conclusions : Through CARE-MND, national audits of MND care and interventions have been possible, leading to protocols for harmonized service provision. Stratification of the MND population is facilitating participation in observational and interventional studies. CARE-MND can act as a template for other neurological disorders.